Electrospun polyetherimide electret nonwoven for bi-functional smart face mask. (April 2017) - Cheng, Yongliang; Wang, Chunya; Zhong, Junwen; Lin, Shizhe; Xiao, Yongjun; Zhong, Qize; Jiang, Hulin; Wu, Nan; Li, Wenbo; Chen, Shuwen; Wang, Bo; Zhang, Yingying; et al.
Abstract: Wearable healthcare devices with monitoring, treating and protecting applications can provide reliable and newfangled interactive service for people. Herein, a bi-functional smart face mask based on electrospun polyetherimide (PEI) electret nonwoven is developed. By virtue of the surplus charges maintained steadily in the PEI nonwoven, the smart face mask possesses bi-functions of removing the particulate matter and generating electricity. Moreover, the unique applications for dynamically monitoring the particulate matter removal ability and human's respiratory rates are demonstrated. Besides offering an unique air filter, this study will promisingly promote the progress of self-powered wearable electronics. Graphical abstract: Highlights: A self-powered smart face mask has been developed. The removal efficiency of sub-micron particulate matter reaches ~99.6%. The mask can act as a self-powered sensor can monitor human's respiratory rates.